2005
DOI: 10.1207/s15374424jccp3402_4
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Traumatic Grief: An Exploration of the Construct in Children Bereaved on September 11

Abstract: This study is an exploration of the measurement and correlates of childhood traumatic grief (CTG). Eighty-three children of uniformed service personnel who died during the World Trade Center attack on September 11, 2001, were assessed using measures of demographic characteristics, trauma exposure (physical proximity, emotional proximity, and secondary adversities), use of coping strategies, psychiatric symptoms (posttraumatic stress disorder [PTSD], general anxiety, depression), self-esteem, and traumatic grie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
1
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 32 publications
8
81
1
6
Order By: Relevance
“…A study (Brown and Goodman 2005) using 83 bereaved children (8-18 years of age) of lost uniformed service personnel during the attacks of 9/11 was conducted to assess the process of normal versus childhood traumatic grief. This study demonstrates the differences between the two types of grief.…”
Section: Impact On Families Of September 11mentioning
confidence: 99%
“…A study (Brown and Goodman 2005) using 83 bereaved children (8-18 years of age) of lost uniformed service personnel during the attacks of 9/11 was conducted to assess the process of normal versus childhood traumatic grief. This study demonstrates the differences between the two types of grief.…”
Section: Impact On Families Of September 11mentioning
confidence: 99%
“…Brown and Goodman's (2005) findings support this regarding the impact of trauma on the 'normal' process of grief for children. They found that children who had lost a parent in 9/11, previously employed in the emergency services, were less likely to be able to access and retain the memory of the parent in this way, because of the intrusion of trauma associated with the parent's death, and this hampered their ability to complete the normal tasks associated with grieving.…”
Section: Link To the Deceased Parentsupporting
confidence: 72%
“…Many studies have demonstrated the development of depression and PTSD in child survivors of trauma and disaster. [100][101][102][103][104] Unrecognized and untreated, acute and posttraumatic stress symptoms can cause lifelong behavioral and mental health problems as a result of changes in brain neurodevelopment and function. These alterations in function create a lifetime risk of subsequent poor school performance, depression, suicidal ideation or attempts, aggression, and risk-taking behaviors.…”
Section: Children's Mental Health During and After Disasters And Traumamentioning
confidence: 99%